Environmental coalitions with heterogeneous countries: Burden-sharing and carbon leakage - Michele Botteon; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 1998)
In this paper a simple model is used to analyse the strategic behaviour of countries that bargain over CO2 emission reductions. Five main world regions are considered and their incentives to sign an international agreement on climate change control are analysed. A non-cooperative approach to coalition formation is used to analyse profitability and stability of the agreement. The main focus of the paper is on the role of carbon leakage. On the one hand, by offsetting the effort of signatory countries, carbon leakage reduces the size of the equilibrium coalition and even the likelihood of a successful negotiation. On the other hand, by increasing the profitability of large coalitions, carbon leakage may stabilise agreements signed by many countries. The paper shows that both the size of leakage and the burden-sharing rule used to share the gains from Cupertino among signatory countries are crucial variables, which explain the type and size of the equilibrium coalitions.
Keywords: C72; C88; H41; 330; Climate change; Leakage effect; Endogenous coalition formation; Burden sharing rules; Non co-operative game theory; Umweltabkommen; Klimaschutz; Treibhausgas-Emissionen; Koalition; Spieltheorie; Theorie